Indium triflate and ionic liquid-mediated Friedländer synthesis of 2-acylquinolines. Issue 21 (2nd November 2017) - Satheeshkumar, Rajendran; Sayin, Koray; Kaminsky, Werner; Rajendra Prasad, Karnam Jayarampillai
ABSTRACT: Friedländer synthesis of 2-acylquinolines from the reaction of symmetrical and unsymmetrical 1, 2-diketones with 2-aminoarylketones in the presence of indium triflate (In(OTf)3 ) and ionic liquid gives quantitative yields. Once the reaction was completed, the catalysts can be recovered and subsequently run for next cycles. Results obtained from theoretical studies have been more strengthened by FT-IR, FT-NMR chemical shifts, and structural parameters which were attained with B3LYP/6-31G(d, p) level of theory and the related results were demonstrated with the experimental interpretations. GRAPHICAL ABSTRACT: